Effectiveness and safety of moxibustion treatment for non-specific lower back pain: protocol for a systematic review. Issue 6 (23rd June 2017) - Leem, Jungtae; Lee, Seunghoon; Park, Yeoncheol; Seo, Byung-Kwan; Cho, Yeeun; Kang, Jung Won; Lee, Yoon Jae; Ha, In-Hyuk; Lee, Hyun-jong; Kim, Eun-Jung; Lee, Sanghoon; Nam, Dongwoo
Abstract : Introduction: Many patients experience acute lower back pain that becomes chronic pain. The proportion of patients using complementary and alternative medicine to treat lower back is increasing. Even though several moxibustion clinical trials for lower back pain have been conducted, the effectiveness and safety of moxibustion intervention is controversial. The purpose of this study protocol for a systematic review is to evaluate the effectiveness and safety of moxibustion treatment for non-specific lower back pain patients. Methods and analysis: We will conduct an electronic search of several databases from their inception to May 2017, including Embase, PubMed, Cochrane Central Register of Controlled Trial, Allied and Complementary Medicine Database, Wanfang Database, Chongqing VIP Chinese Science and Technology Periodical Database, China National Knowledge Infrastructure Database, Korean Medical Database, Korean Studies Information Service System, National Discovery for Science Leaders, Oriental Medicine Advanced Searching Integrated System, the Korea Institute of Science and Technology, and KoreaMed. Randomised controlled trials investigating any type of moxibustion treatment will be included. The primary outcome will be pain intensity and functional status/disability due to lower back pain. The secondary outcome will be a global measurement of recovery or improvement, work-related outcomes, radiographic improvement of structure, quality of life, and adverse events (presence or absence). Risk ratio or mean differences with a 95% confidence interval will be used to show the effect of moxibustion therapy when it is possible to conduct a meta-analysis. Ethics and dissemination: This review will be published in a peer-reviewed journal and will be presented at an international academic conference for dissemination. Our results will provide current evidence of the effectiveness and safety of moxibustion treatment in non-specific lower back pain patients, and thus will be beneficial to patients, practitioners, and policymakers. Trial registration number: CRD42016047468 in PROSPERO 2016